PREPARATION AND PHYSICAL-CHEMICAL AND SENSORIAL ANALYZES OF UXI CREAM (REMUNOM, 2024)
Uxi is a fruit originating from the Amazon, being abundant especially in thestates of Pará and Amazonas, where it is widely consumed by the localpopulation, fresh or as juice, sweets and other forms. This work aimed todevelop and characterize in physical-chemical terms an uxi cream, in addition tocarrying out a sensorial analysis of the product with a view to its acceptance.One hundred untrained tasters participated in the research, 43 women and 57men, aged between 18 and 61 years. The cream had a high rate of generalacceptance, and among men and women, being more accepted by men.Keywords: Amazon; fruit jam; Product of plant origin.